Significance of Parafibromin Expression in Laryngeal Squamous Cell Carcinomas - Inju Cho; Mija Lee; Sharon Lim; Ran Hong (Korean Society of Pathologists & the Korean Society for Cytopathology, 2016)
Background: Parafibromin is a product of the tumor suppressor gene that has been studied as a potential indicator of tumor aggressiveness in the parathyroid, breast, colorectum, and stomach. However, the clinical significance and potential function of parafibromin expression in head and neck squamous cell carcinomas remain largely unknown. The aim of this study was to evaluate the expression of parafibromin in laryngeal squamous cell carcinoma (LSCC) and to verify its potential as a biomarker of tumor behavior. Methods: Parafibromin expression was evaluated in 30 cases of LSCC using immunohistochemistry. The correlations between parafibromin expression and clinicopathologic parameters were investigated. Results: Parafibromin expression was positive in 15 cases (50%) and negative in 15 cases (50%). Tumor size and T stage showed a statistically significant inverse relationship with parafibromin expression (p=.028 and p<.001, respectively). Parafibromin expression was not associated with age, sex, lymph node metastasis, tumor differentiation, or tumor location. There was no statistically significant relationship between parafibromin expression and progression-free survival in the patients (p>.05). Conclusions: Our results indicate that the downregulation or loss of parafibromin expression can be employed as a novel marker of tumor progression or aggressiveness in LSCC.